Analisis Tingkat Kepuasan Pasien Terhadap Pelayanan Rawat Jalan di Klinik Mitra Sehat Sukoharjo - Iik (Universitas Veteran Bangun Nusantara, 2023)
Health is an important thing needed by humans to sustain all of their life activities. The phenomenon of people who prefer to seek treatment abroad rather than using domestic health services is a big challenge. This challenge can be answered by improving quality in all fields, especially in the health sector. So, this is what will help health service providers in determining strategies to meet community needs in the health sector. This study aims to determine the perceptions of outpatients at Mitra Sehat Sukoharjo Clinic. This type of research is descriptive research with a qualitative approach. This research method uses a questionnaire method. The population in this study were the people of Sukoharjo Regency who visited the Puskesmas. The samples taken were 50 respondents. Based on the results of the research that has been done, it can be seen that the public's perception of outpatient services at the Mitra Sehat Sukoharjo Clinic is quite good.